Population, habitat use pattern and feeding behaviour of Irrawaddy squirrel (Callosciurus pygerythrus Geoffroy, 1831) in Jahangirnagar University campus (Jahangirnagar University Journal of Biological Sciences, 2022)
The study was conducted to know the population, habitat use pattern and feeding behaviour of Irrawaddy Squirrel (Callosciurus pygerythrus) in Jahangirnagar University Campus from October 2016 to September 2017. The population density had slightly varied in different months; it was the highest in May (997.58/km2) and the lowest in January (612.98/km2). The mean population density was 841.34/km2 (SD= 135.98). The visibility was the highest at 0900h (15.71%) and the lowest at 1100h (7.07%). The monthly variation was the highest in May (9.88%) and the lowest in January (6.07%), which was probably due to the change of temperature. In total 15 plant species were preferably occupied by the squirrels in Jahangirnagar University Campus. The most preferable tree species was Koroi (Albizia procera) and the frequency was the highest for it as 16.71% of the total sightings of squirrel were in and around Koroi tree. The middle canopy was mostly used (48%) by Irrawaddy Squirrel, followed by lower canopy (29%), upper canopy (10%) and ground (13%). In case of diurnal variation in feeding the highest rate of feeding was recorded in afternoon (at 1700h, 18.46%) and morning (at 0800h, 17.06%). Maximum time spent in feeding was in May 2017(17.40%) and minimum in January 2017 (2.52%). The major items of their diet included fruits and seeds for which they spent 39.4% and 25.4% time, respectively. According to the study, squirrels of Jahangirnagar University Campus were not distributed uniformly, but concentrated in some areas due to vegetation type, food availability and human presence. The study also revealed that the squirrels of Jahangirnagar University campus showed variation in their food choice, feeding behavior and habitat preference.Jahangirnagar University J. Biol. Sci. 10(1 & 2): 19-29, 2021 (June & December)